A Fixed Point Theorem in Orbitally Complete Partially Ordered Metric Spaces. (18th December 2013) - Babu, G. V. R.; Sailaja, P. D.; Kidane, K. T.
Abstract : Let( X, ⪯ ) be a partially ordered set andT : X → X be a mapping. We prove a fixed point theorem for the mapT satisfying a contractive condition in orbits, whenX isT -orbitally complete. Our result extends and generalizes the results of Samet et al. (2013) to partially ordered sets. Also, we generalize the results of Ran and Reurings (2004).